2052. Performance of the Biofire Filmarray Meningitis/Encephalitis Panel in Cryptococcal Meningitis Diagnosis. (26th November 2018) - Walker, Morgan; Sheets, Jeffery; Hamer, Diana; O'Neal, Catherine
Abstract: Background: Diagnosing meningitis and encephalitis is challenging in the immunosuppressed population. Cerebrospinal fluid (CSF) culture is the gold standard diagnostic test for cryptococcal meningitis (CM), but is time intensive and requires a high index of suspicion. The BioFire FilmArray Meningitis/Encephalitis (ME) panel offers an option for rapid diagnostic testing. Recent studies suggest similar performance of the ME panel compared with CSF culture in the initial diagnosis and relapse of CM. We investigated the performance of the ME panel in the diagnosis of cryptococcal disease in patients presenting with meningitis. Methods: A retrospective observational study was performed at an 800 bed regional medical center between June 1, 2016 and March 1, 2018. Laboratory results for all patients admitted with CSF or serum cryptococcal testing were reviewed. We abstracted the results from 14 distinct hospitalizations involving 12 patients (Figure 1) with CM who had an ME panel and CSF culture. Diagnostic performance was determined by comparison of ME panel to CSF culture. Results: The ME panel demonstrated a 71.43% (95% CI: 29.04–96.33) sensitivity and 100% (95% CI: 59.04–100) specificity for diagnosing CM for the population described in Table 1. ME panel detected all four patients with an initial diagnosis of CM and one of three patients with culture positive relapse. Conclusion: Our findings suggest that a negative cryptococcal result on the ME panel should not be used to rule out cryptococcal disease, particularly in patients with a previous diagnosis of CM. Additional testing may increase cost, but until larger studies validate the use of rapid diagnostics, fungal culture remains the gold standard for the diagnosis of CM and should not be eliminated from routine evaluation. Disclosures: All authors: No reported disclosures.